A Comparative Study of the Role of Constant and Logistic Recruitment Rates in Epidemiological Models (Lafia Journal of Scientific and Industrial Research, 2024)
In this paper, we present three mathematical models of epidemiology. In each of the models, we present a scenario where constant and logistic recruitment rate are incorporated in each case. It was observed in Case I that, the reproduction number of the model with logistic recruitment rate is less than the reproduction number from the model with constant recruitment rate. Further, in Case II, the reproduction number from the model with both constant and logistic recruitment rates are the same. Finally, in Case III, it was  observed that the human reproduction number from the model with logistic recruitment rate is higher than the human reproduction number from the model with constant recruitment rate.
Keywords: Constant recruitment rate; Epidemiological models; Logistic recruitment rate; Reproduction number